KEMAMPUAN NUMERASI SISWA PADA MATERI OPERASI PECAHAN DENGAN IMPLENTASI MODEL PROBLEM BASED LEARNING (PBL) - Riska Silvia; Orin Asdarina (Universitas Muhammadiyah Metro, 2024)
The purpose of this research is to see the students' numeracy skills with the application of the Problem Based Learning (PBL) model in solving fraction operation problems in class VII SMP Negeri 2 Blangpidie and the factors that influence the numeracy skills of SMP Negeri 2 Blangpidie students. The design conducted in this research is descriptive research. The subjects in this study were 20 students of class VII of SMP Negeri 2 Blangpidie. Data collection was obtained from giving tests and interviews. From the results of data analysis, it was concluded that students' numeracy skills on fraction operation material in class VII SMP Negeri 2 Blangpidie were in the high category. Students' numeracy ability for indicator I is 83.5%, indicator II is 59.5% and indicator III is 74.7%.